Routine preoperative assessment for cataract surgery is a source of frustration for primary care providers - Donna Ron; Michael Zegans; Catherine L. Chen (BMC, 2024)
Abstract Background Cataract surgery is one of the most common surgical procedures performed in older adults in the United States and is generally considered to be extremely low-risk. As of 2019, routine preoperative evaluation within 30 days of surgery is no longer mandated by the United States of America (USA) Centers for Medicare & Medicaid Services (CMS) for ambulatory surgery centers, but it is unclear how primary care providers perceive this change. Methods We performed a qualitative analysis of semi-structured interviews with six primary care providers to explore primary care providers' perspectives on routine preoperative assessment for cataract surgery. Results Primary care providers commented on the large number of referrals they receive for preoperative assessment before cataract procedures. The analysis revealed an overarching sentiment of resentment over the time, effort, and resources expended on these assessments. Themes included the lack of awareness of the updated regulations that no longer require a history and physical to be completed within 30 days and the perception of a universal lack of medical necessity to perform preoperative assessment for cataract surgery. Providers also commented on the strain on limited resources and the burden on patients. The relationship between specialties and professional roles emerged as another important theme. Conclusions Referrals for preoperative clearance for cataract surgery continue to burden providers, patients, and the health system, and represent an opportunity to streamline care in this patient population.